Analisis Hukum Ekonomi Islam Terhadap Penetapan Fee Transaksi BRILink - Suryani, Eka Yuni (Sharia Faculty Islamic Economic Law Study Department, 2022)
BRILink agent is an officeless banking service expansion initiated by BANK BRI. The presence of BRILink agents really helps the community to take advantage of banking services as needed. In addition, BANK BRI also invites its customers to become BRILink agents, so that they can serve banking transactions to the public, just like coming to a bank or ATM machine. The convenience offered by BRILink to the public raises a separate problem in setting tariffs at the agent level, where BRILink agents have uniform tariffs for their customer transactions. The research tries to reveal the reasons for the difference in tariffs in transactions in each BRILink agent in the Repaking Village, Wonosamodro District, Boyolali Regency and reviews how the fee scheme is in the concept of Islamic Law.